Evaluation of the Stability of Fatty Acids in Erythrocytes from Human Umbilical Cord. Issue 1 (15th January 2020) - Jaramillo, Angela M.; Garmendia, María L.; Muñoz, Patricio; Corbari, Alicia; Valenzuela, Rodrigo; Casanello, Paola
Abstract: The interest in the amount of polyunsaturated fatty acids (PUFA) in the umbilical cord blood (UCB) is increasing, but the stability of erythrocyte PUFA in these samples during storage and washing of the erythrocytes has not been directly evaluated. The purpose of this study was to analyze the effect of the lapse of time on the fatty acid (FA) content from UCB sample collection and maintained at 4 °C (0–12 h) until erythrocyte separation and washing. Palmitic acid (16:0), stearic acid (18:0), 18:1n‐7/n‐9, linoleic acid (18:2n‐6), arachidonic acid (20:4n‐6), 22:4n‐6, eicosapentaenoic acid (20:5n‐3), docosapentaenoic acid (22:5n‐3), and docosahexaenoic acid (22:6n‐3) together accounted for 87% of the FA profile in the umbilical vein erythrocytes. No difference was observed in the concentration of any of the FA studied, nor in the sum of saturated fatty acids (SFA), PUFA, or LC‐PUFA in umbilical erythrocytes obtained at delivery and stored up to 12 h before the separation of erythrocytes. However, if a washing step was included in the processing of the erythrocytes, a decrease in the concentration of 16:0, 18:0, 18:3n‐3, 20:4n‐6, 22:4n‐6, total SFA, PUFA, LC‐PUFA, and n‐6 LC‐PUFA was evidenced, compared to unwashed erythrocytes. The FA concentration in umbilical cord erythrocytes did not change between samples stored from 0 to 12 h until erythrocyte separation. Erythrocyte washing before storage decreased the concentration of significant individual and total SFA, PUFA, and LC‐PUFA. These results should be considered when planning the collection of UCB samples for the study of fatty acid concentration due to the nonscheduled timing of deliveries.